Improving Student Learning Outcomes in Javanese Language Lessons through Quantum Learning and Karsawa Learning Media - Kiky Chandra Silvia Anggraini; Islahiyyah Islahiyyah; Muchammad Bayu Tejo Sampurno (SITTAH: Journal of Primary Education, 2025)
The formulation of the problem in this study is to determine the improvement of student learning outcomes in Javanese language subjects through Quantum Learning and Karsawa learning media. This study chose a quantitative method with a pre-experimental design research design and a one-group pretest posttest design. This study only uses one class with a sample of 21 students who will be given a written test of Javanese learning outcomes twice, namely a pretest before and a posttest after treatment. Based on the study results, the average pretest score was 60.57, and the average posttest score was 84.76. This shows an increase in the posttest score, which is higher than the pretest score in Javanese language lessons. It will be analyzed through the Wilcoxon test statistical test to strengthen this value. The significant number is 0.000 <0.05, indicating that Asymp.Sig. < 0,05. From the results of the hypothesis test, it can be concluded that applying the Quantum Learning method assisted by Karsawa media has an effect on the learning outcomes of class III Javanese language at Madrasah Ibtidaiyah (MI) Mambaul Ulum. The Quantum learning method and Karsawa media can improve Javanese language learning outcomes, especially Javanese characters in students.